Phytochemical Analysis and Bioactivity Assessment of Dichloromethane and Hexane Extracts of Catunaregam spinosa (Thunb.) Tirveng - Baraili, Rabina; Sharma, Khaga Raj (Journal of Nepal Chemical Society, 2026)
Medicinal herbs have long been used by Nepalese communities to cure a variety of ailments, from mild to lethal. The purpose of this study is to estimate the phytochemicals and determine the antioxidant and antibacterial properties of dichloromethane (DCM) and hexane stem bark extracts of Catunaregam spinosa (Thunb.) Triveng. Thin-layer chromatography of extracts using different ethyl acetate/DCM ratios revealed multiple spots, indicating the presence of several non-polar molecules with changing affinity for the mobile phase as well as their chemical variety. The total phenolic content (TPC), total tannin content (TTC), and total flavonoid content (TFC) were determined using the Folin-Ciocalteu phenol reagent and the aluminum chloride colorimetric technique. The DCM crude extract of the stem bark had greater TPC and TTC values of 54.83 ± 1.80 mg GAE/g and 167.58 ± 6.70 mg TAE/g, respectively, but a lower TFC value of 7.65 ± 1.16 mg QE/g compared to the hexane extract. The antioxidant activity of plant extracts was tested in vitro using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical. DCM (IC50 60.18 ± 0.49 μg/mL) showed stronger antioxidant activity than the hexane extract (IC50 72.68 ± 0.26 μg/mL). The agar well diffusion method was used to test the antibacterial activity against Shigella sonnei (ATCC 25931), Escherichia coli (ATCC 25912), Klebsiella pneumoniae (ATCC 700603), and Staphylococcus aureus (ATCC 43300). Since the study found that plant extracts contain an abundance of phenolic and flavonoid compounds, this medicinal plant could be the source of a natural antioxidant and antibacterial agent for future drug development processes.